Teachers matter : rethinking how public schools identify, reward, and retain great educators - Winters, Marcus A. (Lanham : Rowman & Littlefield Publishers, 2012)
"Most of us have had at least one amazing teacher who has inspired, influenced, or encouraged us to do better, aim higher, or just be more confident. However, most of us have also had at least one teacher who has not met our expectations. In Teachers Matter, education researcher Marcus A. Winters, a senior fellow at the Manhattan Institute, argues that our failure to identify and reward high-quality teachers has been devastating for public school students. The question is how do we sort out the good teachers form the bad? Winters shows the shortcomings of the current system that relies on credentials and longevity and spells out a series of reforms based on results achieved in the classroom. For the first time, standardized test results offer an objective, reliable measure of student proficiency that can be tied to an individual teacher. Sure to be controversial, Winters's plan will be of interest to the education community, policy makers, and parent concerned about the future of education in America"--
Includes bibliographical references (p. 131-141) and index.
Keywords: Teachers -- Recruiting -- United States; Public schools -- Faculty -- Recruiting -- United States; Teachers -- Selection and appointment -- United States; EDUCATION / Educational Policy & Reform / General